Digital Marketing Strategy untuk Meningkatkan Daya Saing UMKM Ayam Gepuk Pak Gendut - Rimadias, Santi; Putra, Exan Adityatama; Florencia Irena; Trismi, Jesslyn; Sendjaja, Kenji Manuel; Stephen, Yodi (CV. ITTC INDONESIA, 2023)
Culinary diversity in Indonesia reflects the creativity of the community in developing Micro, Small and Medium Enterprises (MSMEs). MSMEs have a significant contribution to the national economy, although they still face challenges related to the application of digital technology in marketing. This community service aims to implement a digital marketing strategy for MSMEs